Exposure to a novel feedstuff by goat dams during pregnancy and lactation versus pregnancy alone does not further improve post‐weaning acceptance of this feedstuff by their kids. (7th August 2015) - Vu Hai, Phan; Schonewille, J Thomas; Dam Van, Tien; Everts, Henk; Hendriks, Wouter H
Abstract: BACKGROUND: Previous experiments demonstrated the existence of in utero learning in goats. However, in contrast to other animal species, in goats there is no information about the potential of flavour transmission from maternal feed to goat kids during lactation. The aim of the current study was to assess the role of post‐natal exposure of Chromonaela odorata leaf meal (COLM) in relation to the preferences to this feedstuff by goat kids after weaning. It was hypothesised that exposure of COLM to the dams during both pregnancy and lactation versus pregnancy alone, additionally affects post‐weaning intake of COLM by their offspring. RESULTS: Consumption of COLM by the goat kids was similar during the first week post‐weaning for all treatments. However, after 4 weeks the intake of COLM was at least 1.8 times greater when kids were exposed to COLM during pregnancy whereas it remained virtually unchanged when kids were exposed to COLM during lactation only. The increase in COLM consumption was in line with the observations on latency to eat and meal size. CONCLUSION: Transmission of feeding behaviour from goat dams to offspring does not occur during lactation. However, the concept of in utero learning in goats was confirmed. © 2015 Society of Chemical Industry